Development and validation of a flow cytometry antibody test for Lawsonia intracellularis - Baldasso, Débora Zini; Guizzo, João Antônio; Dazzi, Cláudia Cerutti; Paraboni Frandoloso, Gabriela Carolina; Feronato, César; von Berg, Stephan; Carvalho Guedes, Roberto Maurício; Wilson, Heather Lynne; Kreutz, Luiz Carlos; Frandoloso, Rafael (Frontiers in Immunology, 2023)
Lawsonia intracellularis is the etiologic agent of porcine proliferative enteropathy (PPE), an inflammatory bowel disease with a major economic impact on the pig industry. The serological diagnosis of PPE can be performed using Blocking or Indirect ELISA, Immunoperoxidase Monolayer Assay (IPMA) and Indirect Fluorescence Antibody Test (IFAT). Here, we designed a most sophisticated immunological method for the detection of porcine anti-L. intracellularis IgGs, named Flow Cytometry Antibody Test - FCAT. This assay uses whole, live-attenuated L. intracellularis bacteria derived from a commercial vaccine. For the assay, we set up the optimal antigen concentration (106 bacterium/assay), primary antibody dilution (1:100), time of incubation (20 min), antigen stability (15 days), precision (coefficient of variation - CV < 10%), reproducibility (CV  13%) and Receiver Operating Characteristic (ROC). When using a cut-off of >15.15% for FCAT, we determined that it showed a sensitivity of 98.8% and specificity of 100%. The rate of agreement with IPMA was 84.09% with a kappa index of 0.66. FCAT was used to screen 1,000 sera from non-vaccinated pigs housed in 22 different farms and we found that 730 pigs (73%) from 16 farms (72.7%) had L. intracellularis IgG. This high prevalence confirms that L. intracellularis is endemic on Brazilian pig farms. Finally, we determined that FCAT is an easy to perform diagnostic assay and we would highly recommend it for: i) seroepidemiological studies; ii) evaluation of infection dynamics; and iii) characterization of the humoral response profile induced by vaccines.